Law enforcement efforts against bullying perpetrators in school environments - Lubis, Faiz Azhar; Rizal, M. (IHSA Institute, 2024)
Bullying in school environments is a serious problem that has a negative impact on children's development. This study analyzes bullying cases at MAN 1 Medan and finds that the lack of moral and ethical education is one of the main contributing factors. This study also shows that handling bullying cases can be done through legal and non-legal channels. This study uses an empirical normative legal research method by combining analysis of laws and regulations, especially Law Number 35 of 2014 concerning Child Protection, and primary data from interviews. This study aims to examine law enforcement against perpetrators of bullying in school environments. The results of this study indicate that efforts to prevent bullying in educational environments can be done through legal and non-legal channels, especially by referring to Law Number 35 of 2014 concerning Child Protection. This law provides a clear definition of violence against children, including bullying, and provides special protection for children in educational environments. In addition, this study also discusses efforts to prevent bullying through non-legal channels, such as socialization, strengthening awareness of children's rights, and individual approaches. However, further efforts are needed, both through consistent law enforcement and through comprehensive prevention programs in schools, to create a safe and conducive learning environment for all students